ANALISIS KEBUTUHAN SISWA DAN GURU TERHADAP E-MODUL TERINTEGRASI NILAI IMTAQ DI MAN 3 KOTA PEKANBARU - Rohmah, Siti Mashitoh; Robiah, Siti (BIOPENDIX: Jurnal Biologi, Pendidikan dan Terapan, 2024)
Background: This research aims to obtain information on whether students and teachers need an E-Module integrated with IMTAQ values ​​or not. The integrated E-Module of IMTAQ values ​​is an electronic-based module presented in electronic media, either in the form of a computer or Android, which contains writing, images and even videos that contain elements of IMTAQ values. Methods: This research was conducted from 11 December 2023 to 21 December 2023 with the research location at MAN 3 Pekanbaru City and used descriptive qualitative research methods with the aim of describing the benefits of E-Modules for increasing students' IMTAQ scores. Results: Based on the results of interviews conducted by researchers with one of the biology teachers and 10 students in class teach. Conclusion: Based on data analysis, it was found that they needed an E-Module that integrated IMTAQ values.